1997
DOI: 10.1161/01.cir.95.7.1799
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin-Augmented 201 Tl Reinjection Enhances Detection of Reversible Myocardial Hypoperfusion

Abstract: Nitrate-augmented 201Tl reinjection significantly, albeit modestly, improves detection of defect reversibility, especially in patients with coronary collateral circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This is particularly relevant to patients with evidence of collaterals by invasive coronary angiography. 144 Semiquantitative assessment. On rest, reinjection, or redistribution images, myocardial segments with normal perfusion or mild hypoperfusion (score 0 or 1) are viable; moderately hypoperfused segments (scores of 2) represent a combination of viable and nonviable myocardium; and severely hypoperfused segments (scores of C3) represent nonviable myocardium.…”
Section: Myocardial Viabilitymentioning
confidence: 99%
“…This is particularly relevant to patients with evidence of collaterals by invasive coronary angiography. 144 Semiquantitative assessment. On rest, reinjection, or redistribution images, myocardial segments with normal perfusion or mild hypoperfusion (score 0 or 1) are viable; moderately hypoperfused segments (scores of 2) represent a combination of viable and nonviable myocardium; and severely hypoperfused segments (scores of C3) represent nonviable myocardium.…”
Section: Myocardial Viabilitymentioning
confidence: 99%
“…In humans, the effect of nitroglycerin on collateral function has mainly been assessed by means of scintigrams. 5,6 Scintigraphy, however, does not take into account improved myocardial perfusion secondary to nitroglycerin-induced cardiac unloading. [11][12][13] Piek et al found increased coronary collateral flow (Doppler wire technique) after injection of nitroglycerin into the donor coronary artery in patients with spontaneously visible collaterals (n = 24), but not in patients with recruitable collaterals (n = 11).…”
Section: Discussionmentioning
confidence: 99%
“…Although nitroglycerin has been suggested to dilate collateral vessels, most of this information comes from animal experiments or indirectly from perfusion studies in humans. [3][4][5][6] In this prospective study, we aimed to characterize patients with and without coronary collaterals and to evaluate the effects of systemic administration of nitroglycerin on both visible and recruitable coronary collaterals.…”
Section: Introductionmentioning
confidence: 99%
“…5,8 Nitrate administration may further enhance the sensitivity of SPECT to detect VM. 17 SPECT imaging is easily available and lower cost as compared to PET imaging. While normal uptake of radioactive tracer confirms the viability of myocardium, absence of tracer uptake does not confirm nonviable, transmural myocardial scar, as discussed below.…”
Section: Tc 99m Viability Protocolmentioning
confidence: 99%